Pengaruh Prestise dan Gaya Hidup Hedonis Terhadap Keputusan Pembelian Pakaian pada Distro Estizy Collective Kota Bima - Nursalam Rahmatullah; Sri Ernawati; Ismunandar (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This study aims to examine the influence of prestige and hedonistic lifestyle on purchasing decisions for clothing at Estizy Collective, a fashion distributor outlet in Bima City. The research is motivated by the growing fashion consumption trend among youth, driven by the desire for social status (prestige) and pleasure-oriented lifestyles (hedonism). This is a causal associative study using a quantitative approach. Data were collected through questionnaires with a Likert scale distributed to 50 respondents who had made purchases at Estizy Collective. Data analysis techniques include validity and reliability tests, classical assumption tests, multiple linear regression analysis, coefficient of determination, t-tests, and F-tests. The results show that both prestige and hedonistic lifestyle significantly influence purchasing decisions, both partially and simultaneously. The coefficient of determination value of 75.5% indicates that prestige and hedonistic lifestyle have a strong influence on purchasing decisions, while the remaining 24.5% is affected by other factors not examined in this study. Therefore, it is recommended that Estizy Collective maintain its prestige-oriented brand image and strengthen marketing strategies aligned with the lifestyle of its target consumers